Laboratory Testing in Neurorheumatology - Hickey, Meghan K.; Murali, Mandakolathur (Seminars in Neurology, 2014)
Laboratory testing in cases of neuro-rheumatologic disease can be daunting, and the results can be difficult to interpret if not placed in the correct clinical context. To best help our patients and also to practice in a cost-effective environment, laboratory testing must be performed in a logical manner, guided by symptoms and clinical judgment. The authors discuss the different laboratory tests used in the diagnosis and evaluation of rheumatologic diseases often encountered in the practice of neurology. It is important to understand how the tests are performed and which methods are used at your own institution. Testing should be ordered with a specific diagnosis in mind so as not to confuse the clinical picture with possible false-positive results. Through discussion of the various testing options, the authors advocate a step-wise approach to investigation.
Keywords: antinuclear antibodies; extractable nuclear antigen; rheumatoid factor; erythrocyte sedimentation rate; C-Reactive protein anti-SSA; anti-SSB; cryoglobulins; antineutrophilic cytoplasmic antibody; HLA-B51